Esketamine as an Adjuvant to Ciprofol or Propofol Sedation for Same-Day Bidirectional Endoscopy: Protocol for a Randomized, Double-Blind, Controlled Trial With Factorial Design - Long, Yu-qin; Feng, Chang-dong; Ding, Yun-ying; Feng, Xiao-mei; Liu, Hong; Ji, Fu-hai; Peng, Ke (Frontiers in Pharmacology, 2022)
Background: Same-day esophagogastroduodenoscopy and colonoscopy procedures under sedation have been increasingly performed. This study aims to assess the effects of esketamine combined with ciprofol (a novel anesthetic/sedative agent) or propofol on respiratory and hemodynamic adverse events in patients undergoing same-day bidirectional endoscopy. Methods: This is a prospective, randomized, double-blind, placebo-controlled, 2×2 factorial trial. A total of 180 adult patients scheduled for same-day bidirectional endoscopy under sedation will be randomized, in a 1:1:1:1 ratio, to receive 1 of 4 sedation regimens: (1) ciprofol and esketamine, (2) propofol and esketamine, (3) ciprofol and normal saline placebo, or (4) propofol and normal saline placebo. The primary outcome is a composite of desaturation (peripheral oxygen saturation [SpO2] < 95%) and hypotension (mean blood pressure [MBP] < 65 mmHg or decrease in MBP ≥ 20% of baseline) during the sedation and in the recovery room. Secondary outcomes include episodes of desaturation, severe desaturation (SpO2 < 90%), hypotension, severe hypotension (decrease in MBP ≥ 30% of baseline), bradycardia, postoperative nausea and vomiting, dizziness or headache, hallucination or nightmare, injection pain, pain scores and fatigue scores, endoscopist satisfaction, and patient satisfaction. Data will be analyzed on the modified intention-to-treat basis. Discussion: We hypothesize that esketamine as an adjuvant to ciprofol or propofol sedation would improve cardiorespiratory stability. In addition, the potential interactions between interventions will be explored using the factorial design. The results of this trial will provide evidence for daily practice of sedation regimens for same-day bidirectional endoscopy.